2021
DOI: 10.3390/su13063470
|View full text |Cite
|
Sign up to set email alerts
|

Binary Linear Programming as a Tool of Cost Optimization for a Water Supply Operator

Abstract: The problem of scheduling pumps is widely discussed in the literature in the context of improving energy efficiency, production costs, emissions, and reliability. In some studies, the authors analyze the available case studies and compare the results; others present their own computational methods. In the paper, a problem of pump scheduling in regular everyday operations of a water supply operator is considered. The issues of water production optimization and energy savings are part of the topic of sustainable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…The optimization models that are built are implemented in Microsoft Excel's module "Solver" in order to process the calculations [28][29][30]. The task of optimizing non-linear programming is the basis for developing correct conclusions that provide many practical implications in the decision-making process [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The optimization models that are built are implemented in Microsoft Excel's module "Solver" in order to process the calculations [28][29][30]. The task of optimizing non-linear programming is the basis for developing correct conclusions that provide many practical implications in the decision-making process [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In the economic and quality field, binary linear-programming optimization by minimization of the cost, while optimizing environmental pollution and the quality of products, was proposed by [22,23]. Moreover, in the electrical field, integer linear programming was used to maintain energy storage and prolong the battery life cycle, while minimizing load shedding [24].…”
Section: Discussionmentioning
confidence: 99%
“…From the analysis of recent works, it is observed that the emphasis is on the product [17][18][19][20][21][22][23][24][25] and not on the organization. Thus, to eliminate all the shortcomings mentioned above, a multi-criterial optimization was conceived, focusing on economic, environmental, and social development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations